An Analysis Of Student’s Speech Disruption In Student’s Speaking Through Oral Presentation - Yohana Friscila Naibaho; Yessy Octavianna Pasaribu; Harpen Silitonga (Jurnal Ilmu Pendidikan dan Sosial, 2026)
This study aims to analyze speech disruptions experienced by second-grade students of SMA Negeri 14 Medan during oral presentations. Speech disruption, refers to interruptions in the flow of speech that affect fluency and clarity. The research focuses on identifying the types, frequency, causes, and impacts of these disruptions on students’ speaking performance. Employing a qualitative descriptive method, data were collected through classroom observations of students’ oral presentations and semi-structured interviews with selected participants. The speech disruptions were categorized following Gleason and Ratner’s (1998) framework, which includes hesitation, repetition, false starts, and filler words. The findings reveal that repetition is the most dominant type of speech disruption, accounting for 35.80% of occurrences, followed by hesitation (27.78%), filler words (25.30%), and false starts (11.11%). The study also identifies several factors contributing to these disruptions, including lack of preparation, low confidence, nervousness, and limited vocabulary, with lack of preparation being the most significant. These disruptions negatively affect students’ fluency and the effectiveness of their communication, often making it difficult for listeners to follow the intended message. The study suggests that improving students’ preparation, building their confidence, expanding vocabulary, and managing speaking anxiety are crucial strategies to reduce speech disruptions and enhance oral proficiency. This research contributes valuable insights for EFL teachers to better understand and address the challenges faced by students in speaking activities, ultimately supporting the development of more effective teaching approaches to foster fluent and confident English speakers.